Histomorphogenesis of hair follicles and andexa in skin of prenatal goat (Capra hircus) - TRIPATHI, M; MALIK, M R; SHRIVASTAVA, A M; TALUJA, J S (The Indian Journal of Animal Sciences, 2013)
A study was conducted in 60 goat toetuses harvested from gravid uteri and procured from small animal slaughterhouse,Jabalpur. The samples comprised: group 1, up to 10 cm CR length; group 2, 10 to 20 cm CR length; and group. 3, above 20 cm CR length. Development of hair follicles was not evident in the foetuses of group 1. However, the epidermis wasinvaginated to variable extent in the dermis, and a single layer of hair follicles appeared without sebaceous and sweat glandsin group 2. In group 3 the follicles were seen sing.ly or in a group. These were smaller. m size and more in number In thesuperficial dermis than in the deep dermis. The follicles were maximum. (S.13/uDlt area) m neck region and. minmum (5.04/ unit area)in ventralregion. The follicular size and follicular eplthehal thickness revealed nonslgmficant regional differences.